Nanoelectronics, Nanophotonics, And Quantum Technologies: Devices And Applications - Jain, Faquir C.; Broadbridge, C.; Gherasimova, M.; Tang, Hong (World Scientific, 2025)
This timely compendium provides state-of-the-art articles covering research areas in Nanoelectronics, Nanophotonics and Quantum Technologies.Composed of contributions by renowned researchers from both the academia and industry, this useful reference text broadly illustrates relevant aspects of high-performance materials and emerging quantum and nanoscale devices for implementing high-speed electronic systems.
Keywords: Computers / Quantum Computing; Technology & Engineering / Nanotechnology & MEMS; dept.phy

Nanoelectronics, nanophotonics, and quantum technologies - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, Haifeng (Selected topics in electornics and systems, 2025)
Keywords: Field (mathematics); Quantum; Quantum computer; Quantum dot; Quantum entanglement; Quantum technology; dept.phy

Effect of binder concentration on ternary MnO2/CuS/reduced graphene oxide material for supercapacitor applications - Chaudhary, Manika; Oyelola, Lekan; Glidden, Thomas; Broadbridge, C.; LeMaire, Peter; Sharma, Rakesh; Singh, Vinamrita; Sahi, Vikhyat; Singhal, Rahúl (Journal of Solid State Electrochemistry, 2025)
Keywords: Capacitance; Chemical engineering; Chemistry; Electrochemistry; Electrode; Energy storage; Graphene; Inorganic chemistry; Materials science; Metallurgy; Nanotechnology; Oxide; Physical chemistry; Supercapacitor; Synthesis; Ternary operation; Thermodynamics; X-ray diffraction; dept.phy